Краткие результаты работ Инкерманского отряда Севастопольской экспедиции - Кравченко, Э.А.; Лысенко, Р.В.; Савеля, О.Я.; Шевченко, Д.А. (Археологічні дослідження в Україні, 2010)
Preliminary results of the research at Uch-Bash settlement of Kyzyl-Koba culture and of archaeological prospecting in the vicinity of the site are presented.